A Physical Mechanism for Coupling Bone Resorption and Formation in Adult Human Bone - Andersen, Thomas Levin (American Society for Investigative Pathology, 2009)
During skeletal remodeling, pre-osteoclasts and pre-osteoblasts are targeted to critical sites of the bone to resorb and reconstruct bone matrix, respectively. Coordination of site-specific recruitment of these two cell types is a prerequisite to maintain the specific architecture of each bone within strict limits throughout adult life. Here, we determined that the bone marrow microanatomy adjacent to remodeling areas is a central player in this process. By using histomorphometry and multiple immunostainings, we demonstrated in biopsies exhibiting coupled bone resorption and formation that osteoclasts and osteoblasts on the bone surface were always covered by a canopy of flat cells expressing osteoblast markers. In contrast, in biopsies in which this canopy was disrupted, bone formation was deficient. Three-dimensional visualizations revealed that this canopy covered the entire remodeling site and was associated with capillaries, thereby forming a previously unrecognized microanatomical entity. Furthermore, pre-osteoclasts were positioned along these capillaries. These findings led to a model that implicates vasculature in the site-specific recruitment of osteoclasts and osteoblasts and embraces the current knowledge on the molecular mechanism of bone remodeling.